Curcumin Diglutaric Acid, a Prodrug of Curcumin Reduces Pain Hypersensitivity in Chronic Constriction Injury of Sciatic Nerve Induced-Neuropathy in Mice - Thanchanok Limcharoen; Peththa Wadu Dasuni Wasana; Hasriadi; Chawanphat Muangnoi; Opa Vajragupta; Pornchai Rojsitthisak; Pasarapa Towiwat (MDPI AG, 2020)
The drug treatment for neuropathic pain remains a challenge due to poor efficacy and patient satisfaction. Curcumin has been reported to alleviate neuropathic pain, but its clinical application is hindered by its low solubility and poor oral bioavailability. Curcumin diglutaric acid (CurDG) is a curcumin prodrug with improved water solubility and in vivo antinociceptive effects. In this study, we investigated the anti-inflammatory mechanisms underlying the analgesic effect of CurDG in the chronic constriction injury (CCI)-induced neuropathy mouse model. Repeated oral administration of CurDG at a low dose equivalent to 25 mg/kg/day produced a significant analgesic effect in this model, both anti-allodynic activity and anti-hyperalgesic activity appearing at day 3 and persisting until day 14 post-CCI surgery (p < 0.001) while having no significant effect on the motor performance. Moreover, the repeated administration of CurDG diminished the increased levels of the pro-inflammatory cytokines: TNF-α and IL-6 in the sciatic nerve and the spinal cord at the lowest tested dose (equimolar to 25 mg/kg curcumin). This study provided pre-clinical evidence to substantiate the potential of pursuing the development of CurDG as an analgesic agent for the treatment of neuropathic pain.